Pemberian Edukasi dan pelatihan Manajemen Cedera Olahraga Dengan Metode RICE Bagi Siswa Madarasah Aliyah Pondok Putra Ibnu Qoyim Yogyakarta - harditya, trihardi miftahul ulum (LPPM STIKES Madani, 2025)
Sports injuries are a common problem among students, especially at the high school level, where physical activity is often done. Lack of basic knowledge and skills in injury management often leads to inappropriate initial treatment, which can worsen the condition. This community service activity aims to provide education and practical training for 155 students of MA Pondok Putra Ibnu Qoyim Yogyakarta on injury prevention, first aid treatment, and recovery from minor sports-related injuries using the RICE method. This program is carried out through interactive health education sessions, direct simulations of injury management, and case discussions. The implementation of this activity showed 71.61% in student understanding, as well as positive reports regarding changes in attitudes, it can be concluded that this community service has been significantly successful in creating student awareness and preparedness for sports injuries. This initiative is expected to increase student awareness of personal and peer safety during physical activity, as well as promote a culture of safe and healthy sports practices in the school environment.